Influence of Intermittent Hypoxia/Hypercapnia on Atherosclerosis, Gut Microbiome, and Metabolome - Xue, Jin; Allaband, Celeste; Zhou, Dan; Poulsen, Orit; Martino, Cameron; Jiang, Lingjing; Tripathi, Anupriya; Elijah, Emmanuel; Dorrestein, Pieter C.; Knight, Rob; Zarrinpar, Amir; Haddad, Gabriel G. (Frontiers in Physiology, 2021)
Obstructive sleep apnea (OSA), a common sleep disorder characterized by intermittent hypoxia and hypercapnia (IHC), increases atherosclerosis risk. However, the contribution of intermittent hypoxia (IH) or intermittent hypercapnia (IC) in promoting atherosclerosis remains unclear. Since gut microbiota and metabolites have been implicated in atherosclerosis, we examined whether IH or IC alters the microbiome and metabolome to induce a pro-atherosclerotic state. Apolipoprotein E deficient mice (ApoE-/-) mice, treated with IH or IC on a high-fat diet (HFD) for 10 weeks, were compared to Air controls. Atherosclerotic lesions were examined, gut microbiome was profiled using 16S rRNA gene amplicon sequencing and metabolome was assessed by untargeted mass spectrometry. In the aorta, IC-induced atherosclerosis was significantly greater than IH and Air controls (aorta, IC 11.1±0.7% vs IH 7.6±0.4%, p<0.05 and vs Air 8.1±0.8%, p<0.05). In the pulmonary artery (PA), however, IH, IC and Air were significantly different from each other in atherosclerotic formation with the largest lesion observed under IH (PA, IH 40.9±2.0% vs IC 20.1±2.6% vs Air 12.2±1.5%, p<0.05). The most differentially abundant microbial families (p<0.001) were Peptostreptococcaceae, Ruminococcaceae and Erysipelotrichaceae. The most differentially abundant metabolites (p<0.001) were tauro-β-muricholic acid, ursodeoxycholic acid, and lysophosphoethanolamine(18:0). We conclude that IH and IC a) modulate atherosclerosis progression differently in distinct vascular beds with IC, unlike IH, facilitating atherosclerosis in both aorta and pulmonary artery; and b) promote an atherosclerotic luminal gut environment that is more evident in IH than IC. We speculate that the resulting changes in the gut metabolome and microbiome interact differently with distinct vascular beds.